Analisis Faktor-Faktor Yang Mempengaruhi Keberlanjutan UMKM di Aceh Timur - Ronaelia; Tamara, Tamara (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
The sustainability of Micro, Small, and Medium Enterprises (MSMEs) is a crucial aspect in supporting national economic growth. This study aims to analyze various internal and external factors influencing the sustainability of MSMEs. Internal factors include managerial capabilities, leadership, product quality, and technological adaptation. Meanwhile, external factors involve access to capital, market competition, government support, and socio-economic conditions. The analysis reveals that MSMEs with strong innovation, adaptability to technological changes, and optimal use of external support have a higher chance of sustainability. Therefore, an integrated strategy involving collaboration among MSME actors, the government, and the private sector is essential to strengthen the resilience and sustainable growth of MSMEs.